Tunneled peripherally inserted central catheter versus non-tunneled and its effects in clinical outcomes: A multicenter randomized clinical trial protocol - Rodrigo do Nascimento Ceratti; Knut Taxbro; Vineet Chopra; Leandro Augusto Hansel; Carolina Geske Salini; Ivana Duarte Brum; Marina Junges; Arlene Gonçalves dos Santos; Eneida Rejane Rabelo-Silva (PLoS ONE, 2026)
Background The use of peripherally inserted central catheters (PICC) has increased due to its benefits, such as greater durability, safety, comfort, and cost-effectiveness. Technological advancements, such as catheter tip navigation systems and the use of ultrasound, have improved its quality. However, complications still occur, including infections and thrombosis, especially in oncology and intensive care patients. Studies indicate that advanced practices, technology, and specialized teams reduce these risks. New techniques, such as tunneled insertion, show potential for reducing complications, but further research with larger samples is needed to validate these findings. Objective To compare the tunneling technique of PICC to non-tunneling insertion technique regarding the incidence of isolated or combined outcomes of catheter-related bloodstream infection, thrombosis, occlusion, and accidental dislodgement in the adult population within a 30-days period. Materials and methods In this randomized, parallel, multicenter clinical trial, 840 patients from three reference hospitals will be assigned to two parallel groups (conventional PICC and tunneled PICC groups) through computer-generated stratified randomization. The conventional group will undergo PICC insertion according to routine practice. In the tunneled PICC group, an additional subcutaneous tunneling procedure will be performed. Patients will be followed until PICC removal for any reason or 30 days after insertion, whichever occurs first. The primary outcome is to assess whether subcutaneous tunneling reduces the rate of isolated or combined adverse events (infection, thrombosis, obstruction, and dislodgement) compared to the conventional method. Discussion Subcutaneous tunneling is a widely used method to reduce complications associated with catheters. However, its application in PICC has not yet been extensively explored, especially in Brazil. A randomized clinical trial is necessary to objectively assess the effects of subcutaneous tunneling in PICC insertion. This protocol aims to provide evidence on the effectiveness of this technique in reducing complications. Trial registration Clinical Trials platform NCT06365528